2019
DOI: 10.11114/aef.v6i4.4322
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Transmission Among Oil Price, Exchange Rate and Agricultural Commodities Prices

Abstract: The aim of this article is to examine the interdependence relationship among the volatilities of crude oil price, U.S. dollar exchange rate, and a set of agricultural commodities prices. An autoregressive (AR) with an exponential generalized autoregressive conditional heteroscedasticity (EGARCH) model or AR-EGARCH process and vector error correction model (VECM) approach was used on monthly data spanning from Jan 1986 to Dec 2005 as the pre-crisis period and from Jan 2006 to Nov 2015 as the post-crisis period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…11, No. 11;2019 filtered inflation rate and also a non-significant positive relationship between income inequality and the HP filtered squared for the developing countries. The coefficient of inflation gap or the cyclical component of inflation rate is negative, but it is not significant.…”
Section: The Estimation Results For Developing Countriesmentioning
confidence: 92%
See 2 more Smart Citations
“…11, No. 11;2019 filtered inflation rate and also a non-significant positive relationship between income inequality and the HP filtered squared for the developing countries. The coefficient of inflation gap or the cyclical component of inflation rate is negative, but it is not significant.…”
Section: The Estimation Results For Developing Countriesmentioning
confidence: 92%
“…11, No. 11;2019 cointegration analysis and found that income inequality has a positive long-run relationship with economic growth, and inflation. The results confirmed the existence of Kuznets hypothesis in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a Structural Vector Autoregressive (SVAR) models, Siami‐Namini and Hudson () found that a U.S. monetary contraction has a negative significant effect on the aggregate commodity price index and commodity subindices included the food price index, agricultural raw materials price index, maize (corn) price, and crude oil price, and results reinforce the overshooting hypothesis. Also, in another study, Simai‐Namini and Hudson () found that the volatility of the U.S. dollar exchange rate is transmitted to international agricultural commodity prices.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Joining this argument, Wang et al [53] explain that oil shocks have minimal effect on agricultural commodity prices in pre-crisis periods, while it is higher in post-crisis period. Corroborating this argument, Siami-Namini and Hudson [56] argue that prices of food do not significantly react to oil price volatility spillover in pre-crisis period but do in and post-crisis period. Hence, our study employs monthly data spanning from January 2000 to December 2016 dividing the periods into pre-crisis (from January, 2000 to April, 2006) and post-crisis (from May, 2006 to December, 2016).…”
Section: Types and Sources Of Datamentioning
confidence: 99%